2000
DOI: 10.1110/ps.9.8.1439
|View full text |Cite
|
Sign up to set email alerts
|

Blue copper proteins: A comparative analysis of their molecular interaction properties

Abstract: Blue copper proteins are type-I copper-containing redox proteins whose role is to shuttle electrons from an electron donor to an electron acceptor in bacteria and plants. A large amount of experimental data is available on blue copper proteins; however, their functional characterization is hindered by the complexity of redox processes in biological systems. We describe here the application of a semiquantitative method based on a comparative analysis of molecular interaction fields to gain insights into the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 77 publications
0
111
0
Order By: Relevance
“…Wt azurin, which forms a stable complex at the N-terminal to mid-region of p53 (16) without affecting p53 oligomer formation, mostly directs p53 specificity toward activation of the bax gene, leading to apoptosis (9,10). The hydrophobic patch of azurin is known to be involved in protein-protein interaction with its in vitro electron transfer partners (12)(13)(14). A replacement of two hydrophobic amino acids by polar amino acids in this region changes the way the M44KM64E mutant azurin interacts with p53, suppressing its oligomer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wt azurin, which forms a stable complex at the N-terminal to mid-region of p53 (16) without affecting p53 oligomer formation, mostly directs p53 specificity toward activation of the bax gene, leading to apoptosis (9,10). The hydrophobic patch of azurin is known to be involved in protein-protein interaction with its in vitro electron transfer partners (12)(13)(14). A replacement of two hydrophobic amino acids by polar amino acids in this region changes the way the M44KM64E mutant azurin interacts with p53, suppressing its oligomer formation.…”
Section: Discussionmentioning
confidence: 99%
“…On entry into such cells, the WT azurin formed a complex with the tumor suppressor protein p53, stabilized it to raise its intracellular level, generated enhanced levels of reactive oxygen species, and induced apoptosis (9,10). Azurin has a hydrophobic patch exposed to the surface that is believed to be involved in protein-protein interaction with its in vitro electron transfer partners such as cytochrome c 551 (12)(13)(14). When two methionine residues in this hydrophobic patch were replaced by two polar amino acids (lysine and glutamic acid) to reduce the hydrophobicity of the patch, the resultant M44KM64E mutant azurin could still enter the J774 cells, as determined by immunoblotting of the subcellular fractions of the cells incubated for various times with the mutant azurin protein, but demonstrated very little cytotoxicity and induction of apoptosis in J774 cells (15).…”
mentioning
confidence: 99%
“…In contrast to several related ␤ -proteobacteria (e.g. from the genus Alcaligenes ), R. eutropha H16 does not encode blue-copper type single-electron mediators like cupredoxin, azurin, or pseudoazurin [De Rienzo et al, 2000;Farver and Pecht, 1991]. More than 60 genes for putative cytochrome c proteins are present in the genome.…”
Section: Electron Carriersmentioning
confidence: 98%
“…Azurin, a member of the cupredoxin family of redox proteins present in bacteria and green plants, is a type I copper-containing soluble protein (10-14 kDa) that transports electrons during denitrification and photosynthesis (1). We and others have shown that azurin preferentially enters cancer cells (2)(3)(4)(5) and induces a p53-mediated apoptosis in murine J774, human breast cancer, melanoma (2,3,5), and osteosarcoma cells but not in p53-negative osteosarcoma and normal liver cells (p53 wild-type; ref.…”
Section: Introductionmentioning
confidence: 99%